(untitled) (Proceedings of Southern Federal University. Philology, 2014)
Key words: mythopoetic model, fantasy, art world, conflict, chronotope. The article discusses myth and poetic models reflected in the fiction stories and novels by V.P. Krapivin and dilogy of the Tatar writer N. Izmailov “Ubyr”. Special attention is paid to the features of chronotope in these works, originality shown in these conflicts, as well as mythological play between illusion and reality, help readers make sense of the dialectical confrontation between good and evil, life and death. Spatial images in the works of the two writers have a lot in common, a special place in Krapivin and Izmailov’s works take symbols of Roads, Field, Home and opposition Nature - Civilization. We should also note the similarity of conflict reflected in the dilogy of the Tatar writer and works of fiction by V.P. Krapivin. A characteristic feature of confrontations depicted in them is interference in the lives of people of supernatural power. Thanks to this intercession characters begin to live simultaneously in multiple parallel worlds, making them not only interpenetrating, but more plastic. As a result, many of the characters and novels of V.P. Krapivin, like the character of N. Izmailov, are a kind of initiation rite, but often this ritual is symbolic. Writer always leaves boys, endowed with a special gift, a chance to overcome all obstacles, while remaining friendly and not professional hunters for the evil.